Implementasi Metode Simple Additive Weighting (SAW) Dalam Menentukan Siswa-Siswi Terbaik (Studi Kasus: SMAN 6 Tangerang Selatan) - Muhammad AL Hafizh Winarno; Roeslan Djutalov (CV. Multi Kreasi Media, 2025)
The assessment of the best students in schools often faces challenges in determining objective and transparent criteria. This study aims to implement the Simple Additive Weighting (SAW) method to determine the best students at SMAN 6 Tangerang Selatan. The SAW method was chosen for its ability to combine multiple evaluation criteria, such as academic performance, attendance, attitude, and participation in extracurricular activities, to produce a more objective decision. This research adopts a web-based system development approach using PHP as the programming language and MySQL as the database. The results show that the implementation of the SAW method can assist schools in ranking students more efficiently and transparently while reducing subjectivity in the evaluation process.